Representações sociais de professores sobre alunos com altas habilidades: uma contribuição da psicologia social comunitária - Doi, Francislaine Wiczneski (2018)
This study is a qualitative research with the purpose of knowing the social representations (SR) of teachers about students with High Abilities/Giftedness (HA/GD). The student with HA/GD faces daily exclusions, veiled or explicitly. Many professionals do not know exactly how to deal with this population with high intellectual potential and marked differences. The literature has presented myths that are shared contributing to the increase of the exclusion of this population. It was considered necessary to know which representations are present in the reports of elementary school teachers of a state school of Curitiba. The data collected were the subject of categorical thematic analysis. Two categories were identified: characteristics of students with HA/GD – referring to the SR found in the reports; and Teacher‟s Practices with students HA/GD – related to the social practice by the teachers. These categories indicated that these teachers see students with HA/GD with extremely high intellectual potential, accelerated thinking that can reflect in agitated behavior, potentially generating indiscipline and difficulties on the professionals‟ side. The data show the need for better training for the teachers, so that they can mediate a specialized support, so that this student can achieve full development in their areas of interest. This study contributes with reflections on actions that promote a more inclusive view by the community of teachers, contributing to the development of an active stance and social transformations for this discriminated population.